COVID-19 interruptions and SMEs heterogeneity: Evidence from Poland - Monika Wieczorek-Kosmala; Joanna Błach; Anna Doś (Risks, 2021)
This study contributes to the emerging stream of the literature on the COVID-19-related risks and their impact on businesses' performance. The growing evidence within is, however, missing the uniqueness of country-level settings, as well as lacking the voice of SMEs solely. The extant literature provides some evidence on SMEs' vulnerabilities to the crisis, but it commonly compares SMEs with large firms. To cover this gap, the main aim of this study is to analyze the perception of COVID-19 interruptions by various groups of Polish SMEs. Thus, this work adds primarily by revising the perceptions of COVID-19 risks, given the heterogeneity of SMEs if we consider their size, age, legal form of organization and status of a family firm. Based on the survey results on SMEs operating in Poland, we employ ANOVA and k-means ranks to provide strong evidence that COVID-19's impact was perceived as more interruptive by micro and very young firms, as well as by the firms that perform as sole proprietorships. We have also found evidence that family firms do not differ from non-family ones in the perceptions of COVID-19 impacts.
Keywords: 330; business interruptions; COVID-19; Poland; risk; SMEs